Systematic approach in petroleum personnel competence assessment; IOP Conference Series: Earth and Environmental Science; Vol. 43 : Problems of Geology and Subsurface Development - Romanyuk V. B. Vera Borisovna; Nekhoda E. Evgeniya; Dmitriev A. Yu. Andrey Yurievich; Khudyakov D. V. Dmitry Vladimirovich; Pozdeeva G. P. Galina Petrovna (Petroleum Engineering Economics and Mining Law, 2016)
Title screen